Scrum solo application in a project with a strong integration component - Brito, João N. (2020)
In Portugal, 90% of software developing companies are micro companies. In 2002, in the Brazilian market, about 60% of the software developing companies would start their activities with just a single developer (Pagotto, Fabrti, Lerario, and Gonçalves, 2016). The Scrum Solo methodology was developed having in mind, that there is a big need for organizing and managing the software development of teams comprised by a single individual. The underlying complexity of big systems and the underlying integration complexity makes the usage of techniques and processes that guarantee the control of the project vital. The methodology described in this document is validated with two application cases in a context of development. The first one is an extensive project, with strong integration component, and the second one the development of an application for process dematerialization. The Scrum Solo methodology performed well in both cases despite their differences. Nevertheless, more cases should be analysed with the emphasis in using different contexts namely other organizations.